Bildungsbürgertum und völkische Ideologie : Konstitution und gesellschaftliche Tiefenwirkung eines Netzwerks völkischer Autoren (1919-1959) - Vordermayer, Thomas (2016)
The moderate folk-nationalist (völkisch) authors Hans Grimm, Erwin Guido Kobenheyer, and Wilhelm Stapel found great appeal among the German social elites. The author analyzes the ideological proclivity of the Weimar educated middle class and the personal networks, construction of self-image, and mentality of völkisch-oriented intellectuals between the end of the First World War and early West Germany.